Clinical Use of Melatonin as a Cross-Sectional Modulator of Oxidative Stress Across the Perinatal Continuum: From Placental Dysfunction to Neonatal Disease - Francesco Cipriani; Elisa Furlan; Luisa Lonoce; Elisa Laschi; Michele Minerva; Lorenzo Perilli; Federica Lotti; Salvatore Grosso (Nutrients, 2026)
Oxidative stress is a central mechanism linking placental dysfunction, fetal injury, and neonatal disease, supporting the concept of a perinatal oxidative stress continuum that begins during abnormal placentation and may persist after birth. This narrative review explores the biological rationale and current experimental and clinical evidence for melatonin as a potential multitarget intervention across this continuum. Melatonin combines direct antioxidant activity with mitochondrial protection, anti-inflammatory and anti-apoptotic effects, and modulation of endogenous antioxidant defenses and redox homeostasis. Evidence from placental, fetal, and neonatal studies suggests potential protective effects in pregnancy complications and in neonatal conditions characterized by oxidative injury, including hypoxic–ischemic encephalopathy, bronchopulmonary dysplasia, necrotizing enterocolitis, neonatal sepsis, and retinopathy of prematurity. The review was informed by a non-systematic search of PubMed/MEDLINE, Scopus, Web of Science and Cochrane Library for relevant literature published up to 2026, including preclinical and clinical studies, systematic reviews, and relevant clinical trial registrations. Overall, although preclinical evidence is encouraging and early clinical studies suggest potential safety and biological activity, translation into clinical practice remains limited by heterogeneous study designs, dosing and timing regimens, and the lack of adequately powered randomized trials. Further research is needed to establish optimal dosing, timing, patient selection, pharmacokinetic–pharmacodynamic relationships, and long-term safety and efficacy.